2021
DOI: 10.1021/acsanm.1c00282
|View full text |Cite
|
Sign up to set email alerts
|

Confining Palladium Nanoparticles in Microporous Tetrastyrene Polymer Enables Efficient Size-Selective Heterogeneous Catalysis

Abstract: Heterogeneous catalysts with tunable micropores and confined metal sites in micropores are of great significance in sizeselective catalysis but remain difficult to be achieved in organic polymers. In this work, we provide a micropore-confining strategy for the design of size-selective heterogeneous catalysts and investigate their size selectivity on various catalytic reactions. The palladium (Pd) @microporous tetrastyrene polymer (MTP) was synthesized via a Pdcatalyzed coupling reaction, where superfine Pd nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…A conjugated microporous polymer (CMP) is a kind of P-π conjugated polymeric porous material with permanent micropores and a three-dimensional network. At present, the research on CMPs is widely distributed in the fields of multigas adsorption, small-molecule gas–liquid separation, , metal catalysis, , photocatalysis, energy storage, , optical sensors and so on. Compared with traditional molecular sieves and activated carbon, organic porous polymers have the potential to be promising materials for the adsorption of organic dyes through molecular design and functional modification.…”
Section: Introductionmentioning
confidence: 99%
“…A conjugated microporous polymer (CMP) is a kind of P-π conjugated polymeric porous material with permanent micropores and a three-dimensional network. At present, the research on CMPs is widely distributed in the fields of multigas adsorption, small-molecule gas–liquid separation, , metal catalysis, , photocatalysis, energy storage, , optical sensors and so on. Compared with traditional molecular sieves and activated carbon, organic porous polymers have the potential to be promising materials for the adsorption of organic dyes through molecular design and functional modification.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al reported a one-step strategy for the design of size-selective heterogeneous catalysts, which was composed of microporous polymer carriers and ultrafine Pd NPs. This research will expand the application scope of microporous organic polymers in sizeselective heterogeneous catalysis (Scheme 15) [162]. Product selectivity is attributable to the size selectivity of micropores.…”
Section: Porous Materialsmentioning
confidence: 93%
“…are easy to design as two-dimensional structures with a high degree of conjugation, which is not only conducive to the improvement of conductivity, but also good for dispersing the active centers and stabilizing the ultrane MNPs. 62,63 Unlike the network structures described above, POCs are classically zerodimensional porous materials, exhibiting adjustable conned spaces yet generally good solubility. They can be used to prepare soluble and stable ultrane MNPs to obtain special nano-catalytic materials between heterogeneous and homogeneous catalysts.…”
Section: Pmm-confinement Strategies To Synthesize Ultrafine Nanostructuresmentioning
confidence: 99%